Modeling the limiting performance of resistive superconductor fault current limiters for 2G HTS tape - Yılmaz, Buğra; Gençoğlu, Muhsin Tunay (Fırat University, 2022)
Fault currents in power systems force valuable power system elements thermally, electro-dynamically and electromagnetically. Due to the increase in fault current levels, the installation of components resistant to fault currents and the damage of these currents to existing components bring economic problems. Therefore, various modern limiting methods have been developed in recent years. One of these methods, Resistive Superconducting Fault Current Limiter (R-SFCL), increases the security and sustainability of the system by eliminating these risks. This study made a dynamic model in MATLAB/Simulink by creating a sample R-SFCL in the laboratory using a 2G HTS (High-Temperature Superconductor) tape. With this model, the limitation analysis for single phase-ground fault is observed. The simulation results and the responses of the sample R-SFCL were compared and it was concluded that they showed a great deal of similarity.
Keywords: Electrical Engineering; Elektrik Mühendisliği